Microbial Community and Fermentation Characteristics of Native Grass Prepared Without or With Isolated Lactic Acid Bacteria on the Mongolian Plateau - You, Sihan; Du, Shuai; Ge, Gentu; Wan, Tao; Jia, Yushan (Frontiers in Microbiology, 2021)
This study aimed to isolate, characterize and identify wild lactic acid bacteria (LAB) strains from native grass silage on the Inner Mongolian Plateau, and assessed their effects on fermentation quality and microbial community of native grass silage. Three isolated strains were Gram-positive, homofermentative, catalase-negative, not produce gas from glucose. These strains could grow normally at pH 4.0–8.0, 15–30 ˚C and NaCl 3% and 6.5%. The three strains and a commercial inoculant were used as additives. Lactic acid bacteria (LAB) effectively improved silage quality. After fermentation, Lactobacillus plantarum was the dominant species in all silages, which the L, XM2 and 265 inoculated silages led to higher (P<0.05) lactic acid content. This study demonstrated that the addition of LAB can change the microbial community and influence silage fermentation. The strain XM2 performed better and is a potential starter culture for native grass silage.